Objective structured assessment of veterinary students’ suture skills before and after training in theory and practice - Rodríguez, Maria Paz; Marinkovic, Boris; Ale, Nicolas; Santis, Paulina; Arias, Jose Ignacio (Austral Journal of Veterinary Sciences, 2025)
This study evaluated the effectiveness of the Objective Structured Assessment of Technical Skills (OSATS) in measuring and improving veterinary students’ proficiency in simple suturing. Forty final-year veterinary students participated in a structured training session that included theoretical instruction, video demonstrations, and hands-on practice sessions. Performance was assessed pre- and post-training using the OSATS, incorporating both a global rating scale and a procedural checklist. Before training, only 50% of the students met the passing criteria, with common deficiencies in needle handling, suture placement, and wound-edge eversion. After the intervention, the pass rate increased to 90%, with significant improvements across most performance indicators (P < 0.05), although deficiencies in movement fluidity persisted. Gender analysis revealed no statistically significant differences in the overall performance. These findings confirm that OSATS is a valid and reliable tool for objectively assessing technical surgical skills in veterinary education. This study supports its integration into veterinary curricula to standardize competency evaluation and enhance training outcomes. Future research should explore its application in diverse surgical procedures and assess long-term skill retention through follow-up assessments. The results offer practical guidance for veterinary educators aiming to develop structured, skill-based learning environments that ensure clinical readiness.